2022
DOI: 10.3390/cimb44090275
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Induces Late Differentiation and Death of Human Oral Keratinocytes

Abstract: Keratinocytes are essential cells for wound repair. Impaired oral wound healing is common in diabetic patients with periodontal disease. High glucose, or hyperglycemia, impairs the cellular function of different cell types. However, it is unknown whether high glucose has a detrimental effect on the functions of oral keratinocytes. In the current study, a human gingival keratinocyte cell line, telomerase immortalized gingival keratinocytes (TIGK), was treated with high glucose (24 and 48 mM) for up to 120 h. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Previous work has shown that a high-glucose environment impairs the migration and proliferation of cultured skin keratinocytes [35][36][37][38]. Our recent study has also shown that high glucose inhibits oral keratinocyte proliferation and migration, induces late keratinocyte differentiation, and causes cell death [9]. Given the pivotal roles of Arg in cell proliferation, we investigated if and how Arg regulated the proliferation of oral keratinocytes especially under high-glucose conditions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous work has shown that a high-glucose environment impairs the migration and proliferation of cultured skin keratinocytes [35][36][37][38]. Our recent study has also shown that high glucose inhibits oral keratinocyte proliferation and migration, induces late keratinocyte differentiation, and causes cell death [9]. Given the pivotal roles of Arg in cell proliferation, we investigated if and how Arg regulated the proliferation of oral keratinocytes especially under high-glucose conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Our study here, for the first time, discovered that Arg enhances the proliferation of oral keratinocytes under both low-and high-glucose conditions. Due to the detrimental pathological effects of high glucose on oral keratinocytes [9] and its clinical relevance to diabetes, our studies were performed under high-glucose conditions. RNA sequencing analyses identified CYP1A1 as the top upregulated DEG at both 24 and 48 h after Arg treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation